International Journal of Sustainable Development & World Ecology - International Journal of Sustainable Development & World Ecology (Taylor & Francis, 2026)
The International Journal of Sustainable Development & World Ecology is a interdisciplinary journal for publishing cutting-edge research with novel concepts and broad significance on socioeconomic and environmental sustainability on the Earth. The aims of the journal are to promote sustainable development that recognises the balance of meeting development opportunities and conserving ecosystem services. Launched in 1994, the journal has reached a worldwide, diversified readership.
FI 1.5
Q1
Keywords: Geography; Planning; Urban & Environment; Ecología; Desarrollo sustentable; Acuerdos transformativos; Transformative agreements; Carbono; Cambio climático; Ecosistemas naturales